Dihydropyridine calcium blockers do not interfere with non-rapid eye movement sleep - Han, GoEun; Matsumoto, Sumire; Diaz, Javier; Greene, Robert W.; Vogt, Kaspar E. (Frontiers in Neuroscience, 2022)
Slow wave or non-rapid eye movement (NREM) sleep is tightly homeostatically regulated and essential for survival. Slow waves are observed in the electro-encephalogram (EEG) as oscillations in the delta (0.5-4 Hz) range. Slow wave activity is to date the best indicator for homeostatic sleep regulation; it is increased after prolonged waking and fades during NREM. The precise mechanisms underlying sleep homeostasis and the generation of slow waves are unknown. Activity-dependent neuronal calcium influx has been hypothesized to play an important role in generating slow oscillations and might be involved in downstream signaling that mediates sleep function. Dihydropyridine blockers of L-type voltage gated calcium channels (VGCCs) are in wide clinical use to treat hypertension and other cardiovascular disorders and are readily blood-brain-barrier penetrant. We therefore wanted to investigate their potential effect on slow wave generation and homeostatic NREM sleep regulation in freely behaving mice. In-vivo two-photon imaging of cortical neurons showed larger spontaneous calcium transients in NREM sleep compared to waking. Application of the dihydropyridine calcium blocker nicardipine significantly reduced cortical calcium transients, without affecting slow wave generation. Nicardipine also did not affect the slow wave activity over 24h following application. Time spent in slow wave sleep and episode duration were also not affected. Thus, acute block of calcium entry through L-type VGCCs does not interfere with slow wave generation or its homeostatic regulation, despite prior evidence from calcium channel knockout mice.